Factors affecting utilization of mental health services in four districts in Zambia - Changwe, Gilbert (Lusaka: University of Zambia , School of Medicine, 2015)
The aim of the study was to determine the factors affecting utilization of mental health services in four districts of Zambia namely, lusaka, Ndola, Samfya and Senanga. The study was conducted among patients, caretakers and members of staff from Maina Soko Soko Military, Ndola Central, Samfya District and Senanga District Hospitals.
A study submitted in partial fullfilment of the requirements for the award of a Bachelor of Science Degree in Nursing.
Includes bibliographical references.
Keywords: Mental health facilities; Mental health services--Zambia.